MEDICAL PROPERTIES OF LAVENDER PLANT (Neo Science Peer Reviewed Journal, 2023)
Lavender flowers, widely used in traditional medical systems and folk medicine, are a promising object for pharmacognostic and pharmacological research. At present, Andijan State University researchers conduct extensive research on the raw material of the medicinal plant - lavender officinalis flowers. The results obtained in the care and adaptation of lavender to the climate of Uzbekistan can be used to develop this type of raw material.